Retrospective chart review and survey to identify adverse safety events in the emergency medical services care of children with out-of-hospital cardiac arrest in the USA: a study protocol. Issue 10 (21st October 2020) - Eriksson, Carl; Schoonover, Amanda; Harrod, Tabria; Meckler, Garth; Hansen, Matt; Yanez, David; Daya, Mo; Jui, Jonathan; Guise, Jeanne-Marie
Abstract : Introduction: Efforts to improve the quality of emergency medical services (EMS) care for adults with out-of-hospital cardiac arrest (OHCA) have led to improved survival over time. Similar improvements have not been observed for children with OHCA, who may be at increased risk for preventable adverse safety events during prehospital care. The purpose of this study is to identify patient and organisational factors that are associated with adverse safety events during the EMS care of paediatric OHCA. Methods and analysis: This is a large multisite EMS study in the USA consisting of chart reviews and agency surveys to measure, characterise and evaluate predictors of our primary outcome severe adverse safety events in paediatric OHCA. Using the previously validated Paediatric prehospital adverse Event Detection System tool, we will review EMS charts for 1500 children with OHCA from 2013 to 2019 to collect details of each case and identify severe adverse safety events (ASEs). Cases will be drawn from over 40 EMS agencies in at least five states in geographically diverse areas of the USA. EMS agencies providing charts will also be invited to complete an agency survey to capture organisational characteristics. We will describe the frequency and proportion of severe ASEs in paediatric OHCA across geographic regions and clinical domains, and identify patient and EMS organisational characteristics associated with severe ASEs using logistic regression. Ethics and dissemination: This study has been approved by the Oregon Health & Science University Institutional Review Board (IRB Approval# 00018748). Study results will be disseminated through scientific publications and presentations, and to EMS leaders and staff through local EMS medical directors, quality and training officers and community engagement activities.